Governance quality and transparency of politics in the European Union - GENÇKAYA, ÖMER FARUK (Palgrave Macmillan, 2022)
Transparency and accountability are the primary prerequisites to an effectively functioning political system in democratic countries. Thereby, good governance and market economy can become more sustainable, and politicians can be prevented from using their political power for private gain instead of the public interest. However, recent democratic decline around the world and, particularly, in several EU member and candidate states, has created a challenge to transparent and accountable financing of politics. This study aims to explore the extent to which recent democratic backsliding has affected the content of regulations and implementation of political financing, and vice versa, in the 27 EU member states, the UK, and seven EU candidate/potential candidate countries. We argue that in the countries where there has been a sharp decline in their corruption perception, democracy, freedoms, civil rights and liberties, and governance scores, it is expected that there will have been regression in the rules, regulations and, in particular, practices of the transparency and accountability of political financing. Our findings indicate that there is no uniform or mutual relationship between the transparency and accountability of political financing, and democracy, freedoms, corruption perception, and governance performance levels, and which appears to be the same for all European countries. In this regard, each country should be evaluated on its own merits.
Keywords: Transparency; Political finance; The EU; Governance; Democracy